Tax fraud indicators / Rohaya Md Noor … [et al.] - Md Noor, Rohaya; Abdul Aziz, Alizan; Mastuki, Nor’Azam; Ismail, Norashikin (Universiti Teknologi MARA Cawangan Selangor, 2012)
This paper examines data of companies subjected to tax investigation during the tax years of 2001 to 2005 to detect the financial ratio associated with tax evasion. Using the financial ratio analysis, the objective of this study is to investigate the possible indicators of fraudulent financial reporting for tax evasion. Six financial ratios applied to a final sample of 73 companies. Univariate and multivariate statistical techniques are used to identify the indicators of fraud financial reporting. Based on the ordinary least square model, this study provides empirical evidence that the ratio of sales, working capital and debts over total assets, are significantly associated with the companies’ tax evasion. Hence, the findings imply that these ratios can be used by tax offices in their investigation as a predictor of fraud financial reporting for tax evasion purposes. The results therefore demonstrate that the findings could be of assistance to tax authorities in their effort to identify the possibility of tax evasion.